Odpowiedź:
a)
- 3/4+ (-8 5/8) +(-6 5/6) + (- 1 3/8) = -6/8 - 8 5/8 - 6 5/6 - 1 3/8 = -8 11/8 - 1 3/8 =-6 5/6 = -9 14/8 - 6 5/6 = -10 6/8 - 6 5/6 = -10 3/4 - 6 5/6 = -10 9/12 - 6 10/12 = -16 19/12 = -17 7/12
b)
- 14 1 /2 + (- 7 3/5 ) +8 1/5 + ( - 6,3) = -14,5 - 7,6 + 8,2 - 6,3 = -22,1 + 1,9 = -20,2
c)
20 + ( - 16, 3) + 4 1/3 + ( - 18 2/3 ) = 24 1/3 - 18 2/3 - 16 3/10 = 5 2/3 - 16 3/10 =
= 5 20/30 - 16 9/30 = 5 20/30 - 15 39/30 = -10 19/30
d)
- 0,6 + 2 3/8 + ( - 7 5/8 ) + ( - 1/2 ) + 0 = -0,6 + 2 3/8 - 7 5/8 - 0,5 = -5 2/8 - 1,1 =
= -5 1/4 - 1,1 = -5,25 - 1,1 = -6,35
Szczegółowe wyjaśnienie: